DEVELOPMENT OF STROKE AMONG THE POPULATION >18-90 YEARS OF AGE AGAINST THE BACKGROUND OF AIR TEMPERATURE FLUCTUATIONS IN THE CLIMATIC CONDITIONS OF SOUTHERN KYRGYZSTAN - Umurzakova G. I.; Mamasaliev N. S.; Murzalieva A. M.; Zubairov Zh. T.; Z. N. Mamasoliev.; B. U. Usmonov (American Journals Publishing, 2023)
Over the past decades, the unprecedented rate of global warming and climate change has been a source of concern. In recent years, climate change has been considered as one of the leading factors influencing public health and the formation of acute and chronic non-communicable diseases. The Fergana Valley of Kyrgyzstan belongs to a different climatic and geographical zone. Residents of the plains and low-mountain regions of southern Kyrgyzstan are more adapted to a hot climate, the effect of which on their health has not been studied using new WHO methodological approaches.
Keywords: Stroke, Kyrgyzstan, air temperature, population